2015
DOI: 10.1002/ardp.201400337
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and In Vitro Antiproliferative Activity of Novel Isatin‐Quinazoline Hybrids

Abstract: Using a molecular hybridization approach, a new series of isatin-quinazoline hybrids 15a-o was designed and synthesized via two different synthetic routes. The target compounds 15a-o were prepared by the reaction of quinazoline hydrazines 12a-e with indoline-2,3-diones 13a-c or by treating 4-chloroquinazoline derivatives 11a-e with isatin hydrazones 14a-c. The in vitro anticancer activity of the newly synthesized hybrids was evaluated against the liver HepG2, breast MCF-7 and colon HT-29 cancer cell lines. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…Arya et al (2014) reported that novel fluorinated benzothiazolo[2,3-b] quinazoline they synthesized via greener approach possessed highly promising photoanti-proliferative activity upon human keratinocytes cell line (Arya et al, 2014) and carcinoma cell line such as HL-60 as well as LoVo cell lines (Arya et al, 2014). Novel array of isatin-based quinazolines have been reported to displayed distinctive selective growth inhibitory effect (IC50 = 1.0 ± 0.2 to 2.4 ± 0.4 μM) by making use of molecular hybridization technique (Fares et al, 2015).…”
Section: Anti-proliferative Activitymentioning
confidence: 99%
“…Arya et al (2014) reported that novel fluorinated benzothiazolo[2,3-b] quinazoline they synthesized via greener approach possessed highly promising photoanti-proliferative activity upon human keratinocytes cell line (Arya et al, 2014) and carcinoma cell line such as HL-60 as well as LoVo cell lines (Arya et al, 2014). Novel array of isatin-based quinazolines have been reported to displayed distinctive selective growth inhibitory effect (IC50 = 1.0 ± 0.2 to 2.4 ± 0.4 μM) by making use of molecular hybridization technique (Fares et al, 2015).…”
Section: Anti-proliferative Activitymentioning
confidence: 99%
“…In 2012, N,N' hydrazine-bis-isatin derivatives 20 (Figure 13 A series of isatin-quinazoline hybrids 21 (Figure 14) was designed by Fares et al [40] in which 3-hydrazinoindolin-2-one is directly attached to quinazoline moiety …”
Section: Figure 13mentioning
confidence: 99%
“…It is a multikinase inhibitor that targets VEGFR-1, VEGFR-2, PDGFRb, and c-Kit. Recently, our research group has paid much attention to develop many novel small molecules based on the indolin-2-one core as potent anticancer agents [14][15][16][17][18][19][20][21][22] . In 2017, we reported two studies 14,15 regarding development of hydrazonoindolin-2-onebased derivatives and evaluation of their anti-proliferative activity against A549 (lung), HT-29 (colon), and ZR-75 (breast) human cancer cell lines, beside evaluation of their pro-apoptotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned findings and in connection with our research program on the development of indolin-2-one-based anticancer candidates [14][15][16][17][18][19][20][21][22] , it was thought worthwhile to extend our investigations to probe certain hydrazonoindolin-2-ones displaying promising anti-proliferative activity. In this study, we reported the design and synthesis of different series of hydrazonoindolin-2-ones 3a-e, 5a-e, 7a-c, and 10a-l, adopting three distinctive strategies to develop such derivatives (Figure 2).…”
Section: Introductionmentioning
confidence: 99%